The Khalimsky Line Topology- Countability and Connectedness - Bhuiyan, S.A (International Journal Of Chemistry, Mathematics And Physics(IJCMP), 2022)
The concepts of connectedness and countability in digital image processing are used for establishing boundaries of objects and components of regions in an image. The purpose of this paper is to investigate some notions of connectedness and countability of Khalimsky line topology.